Distribution of sleeping sites of the Yunnan snub‐nosed monkey (Rhinopithecus bieti) in the Samage Forest, China. Issue 4 (December 2013) - LI, Dayong; GRUETER, Cyril C.; REN, Baoping; LI, Ming; PENG, Zhengsong; WEI, Fuwen
Abstract Sleeping site locations are important to free‐ranging primate groups. Sites are strategically selected by primates so as to optimize security, comfort and foraging efficiency. Data were collected on the distribution of sleeping sites of the Yunnan snub‐nosed monkey (Rhinopithecus bieti) between Sep 2005 and Sep 2006 at Gehuaqing in Baimaxueshan Nature Reserve, China. We identified 54 sleeping sites, which were used 137 times during the study period. These sleeping sites were distributed throughout the monkey group's total home range. R. bieti preferred certain sleeping sites over others: 63% of the sleeping sites were used 2 or more times in 13 months. Groups reused locations in an unpredictable long‐term pattern, but avoided using the same sleeping site on consecutive nights. To reduce the time and energetic costs of travel, monkeys preferred sleeping near commonly used feeding sites. We recorded 124 feeding sites in the home range, which were used 174 times. A total of 27 sleeping sites were also feeding sites, and all remaining sleeping sites were close to feeding sites. There was a positive correlation between the intensity of use of sleeping sites and feeding sites. The present study suggests that the availability and the location of immediate sources of food is a key factor in the choice of sleeping sites.